Nanotechnology Addressing Cutaneous Melanoma: The Italian Landscape - Luigi Battaglia; Anna Scomparin; Chiara Dianzani; Paola Milla; Elisabetta Muntoni; Silvia Arpicco; Roberta Cavalli (MDPI AG, 2021)
Cutaneous melanoma is one of the most aggressive solid tumors, with a low survival for the metastatic stage. Currently, clinical melanoma treatments include surgery, chemotherapy, targeted therapy, immunotherapy and radiotherapy. Of note, innovative therapeutic regimens concern the administration of multitarget drugs in tandem, in order to improve therapeutic efficacy. However, also, if this drug combination is clinically relevant, the patient's response is not yet optimal. In this scenario, nanotechnology-based delivery systems can play a crucial role in the clinical treatment of advanced melanoma. In fact, their nano-features enable targeted drug delivery at a cellular level by overcoming biological barriers. Various nanomedicines have been proposed for the treatment of cutaneous melanoma, and a relevant number of them are undergoing clinical trials. In Italy, researchers are focusing on the pharmaceutical development of nanoformulations for malignant melanoma therapy. The present review reports an overview of the main melanoma-addressed nanomedicines currently under study in Italy, alongside the state of the art of melanoma therapy. Moreover, the latest Italian advances concerning the pre-clinical evaluation of nanomedicines for melanoma are described.